Additional evidence of stable EMF-induced changes in water revealed by fungal spore germination - Rai S.; Singh U.P.; Mishra G.D.; Singh S.P.; Samarketu (My University, 2025)
Spore germination of some fungi was studied in EMF-tieated water samples. Water samples were exposed to 9.575 GHz microwave modulated with square waves of different pulse repetition frequencies. The study indicates varying inhibitory effects of different modulation frequencies on spore germination of Alternaria alternata, A. tenuissima, Fusarium udum, Helminthosorium oryzae, H. turcicumand Ustilago cynodontis. The pulse repetition frequency-dependent variation in spore germination caused by irradiated water illustrates that water may have the capability to store EMF frequency effects. EMF-treated water might have caused the effect by either changing the activities of and/or deactivating the spore enzymes. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.